Negative plate and battery comprising same
By using porous current collector, black phosphorus or its composite negative electrode active material layer and high-temperature resistant material surface coating in the negative electrode sheet, the problem of poor thermal stability of black phosphorus material is solved, and the thermal stability of the battery is significantly improved and Security.
Patent Information
- Application Number
- CN202411566280.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
AI Technical Summary
Black phosphorus materials have poor thermal stability during charging and discharging of lithium batteries, which can easily cause spontaneous combustion and lead to battery safety problems.
A negative electrode sheet is designed, including a porous current collector, a negative electrode active material layer and a surface coating of a high temperature resistant material. The negative electrode active material layer contains black phosphorus or a composite thereof, and the surface coating contains ceramic material and/or organic polymer with a thermal decomposition temperature of ≥200°C.
It significantly improves the thermal stability of the negative electrode sheet, prevents spontaneous combustion, improves the electrochemical performance and service life of the battery under high temperature conditions, and enhances the safety of the battery.
Smart Images

Figure CN119400803A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and in particular to a negative electrode sheet and a battery comprising the same. Background Art
[0002] As an allotrope of phosphorus, black phosphorus has excellent conductivity and interlayer spacing suitable for ion shuttling. When black phosphorus is used as the negative electrode material of lithium batteries, it enables lithium ions to achieve efficient insertion and extraction processes during the charging and discharging process. The high performance of batteries using black phosphorus as negative electrode active materials is mainly due to the high specific capacity and excellent conductivity of black phosphorus materials. Compared with traditional graphite negative electrode materials, black phosphorus applied to lithium batteries shows higher initial discharge and charging specific capacity (2243.9mAh / g, 1279mAh / g), and has higher energy density, which means that it can store more energy at the same weight or volume. In addition, the interlayer spacing of black phosphorus is more suitable for ion shuttling, which helps to improve the charging speed and energy efficiency of the battery. Therefore, batteries using black phosphorus as negative electrode active materials can theoretically achieve faster charging speeds and higher energy density, provide longer driving range for mobile devices such as electric vehicles, and bring great changes to new energy vehicles and electronic information industries. However, due to the poor thermal stability of black phosphorus materials, especially the excessive temperature rise during charging and discharging (over 40°C), it is easy to spontaneously combust and cause battery safety problems. At present, the industry mainly uses black phosphorus materials as negative electrode active materials by combining them with other materials, such as graphite, graphene and other materials. However, it still cannot effectively solve the problem that black phosphorus materials themselves have poor thermal stability and are prone to spontaneous combustion, which may cause battery safety problems. Summary of the invention
[0003] The present application provides a negative electrode sheet and a battery comprising the same, aiming to solve the problem of poor thermal stability of existing batteries to a certain extent.
[0004] In a first aspect, the present application provides a negative electrode sheet, which includes a porous current collector, a negative electrode active material layer arranged on at least one surface of the porous current collector, and a surface coating arranged on the side of the negative electrode active material layer away from the porous current collector, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes black phosphorus or a black phosphorus composite, and the surface coating includes a high temperature resistant material, the high temperature resistant material includes a ceramic material and / or an organic polymer with a thermal decomposition temperature of ≥200°C.
[0005] In an optional embodiment, the black phosphorus composite comprises one or more of a composite of black phosphorus and an organic material and a composite of black phosphorus and an inorganic material.
[0006] In an optional embodiment, the composite of black phosphorus and inorganic material comprises one or more of a black phosphorus-graphite composite and a black phosphorus-graphene composite.
[0007] In an optional embodiment, the composite of black phosphorus and organic material comprises a black phosphorus-polyacrylonitrile composite, a black phosphorus-polyvinylidene fluoride composite, or a black phosphorus-polyimide composite.
[0008] In an optional embodiment, the thickness of the porous current collector is 4-15 μm; and / or the pore size of the porous current collector is 50-100 μm, the pore spacing of the porous current collector is 100-200 μm, and the porosity of the porous current collector is 5-50%.
[0009] In an optional embodiment, the particle size D90 of the negative electrode active material in the negative electrode active material layer is 20-800 nm, and the particle size D50 is 300-600 nm.
[0010] In an optional embodiment, the ceramic material includes one or more of boehmite and alumina.
[0011] In an optional embodiment, the organic polymer having a thermal decomposition temperature of ≥200° C. comprises one or more of polyimide, polymethyl methacrylate, and polyvinylidene fluoride.
[0012] In an optional embodiment, the alumina has a particle size D50 of 0.2-6 μm and a specific surface area of 10-300 m 2 / g.
[0013] In an optional embodiment, the surface coating further includes one or more of a conductive agent and a binder.
[0014] In an optional embodiment, based on the total mass of the surface coating being 100%, the mass of the high temperature resistant material accounts for 70-96%, the mass of the conductive agent accounts for 1-15%, and the mass of the binder accounts for 3-15%.
[0015] In an optional embodiment, the negative electrode active material layer further includes one or more of a conductive agent and a binder.
[0016] In an optional embodiment, based on the total mass of the negative electrode active material layer being 100%, the mass of the negative electrode active material accounts for 90-99%, the mass of the conductive agent accounts for 0-2%, and the mass of the binder accounts for 1-8%.
[0017] In an optional embodiment, the permeability index R of the negative electrode sheet is 6.0 to 101, preferably 40 to 80;
[0018] Wherein, the permeability index R is calculated by the following formula (I):
[0019]
[0020] in,
[0021] A is the pore size of the porous current collector, in μm;
[0022] B is the particle size D50 of the negative electrode active material, which is the particle size value corresponding to the cumulative distribution percentage from small to large reaching 50% in the particle size distribution, in nm;
[0023] W is the porosity of the porous current collector;
[0024] Among them, the porosity W has the following relationship per unit area through the pore size and pore spacing of the porous current collector:
[0025]
[0026] C is the pore spacing of the porous current collector, in μm;
[0027] In an optional embodiment, the single surface density of the negative electrode active material layer is 20 to 60 g / m 2 , the single-side thickness is 10 to 30 μm.
[0028] In an optional embodiment, the surface coating has a single-sided surface density of 2 to 10 g / m 2 , the single-side thickness is 1 to 7 μm.
[0029] In a second aspect, the present application provides a battery, comprising the positive electrode sheet described in the first aspect of the present application, and further comprising a separator, a positive electrode sheet and an electrolyte.
[0030] In an optional embodiment, the diaphragm includes a base film and a coating layer provided on at least one surface of the base film; preferably, the coating layer contains one or both of polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA).
[0031] In an optional implementation, the single-side thickness of the adhesive layer is 1 to 3 μm.
[0032] In an optional embodiment, the relationship between the single-side thickness y of the negative electrode active material layer and the single-side thickness x of the coating layer is: y / x=3.33-30.
[0033] In an optional embodiment, a ceramic layer is further provided between the base film and the adhesive layer.
[0034] The technical solution of this application has the following advantages:
[0035] The negative electrode sheet provided by the present application includes a porous current collector, a negative electrode active material layer disposed on at least one surface of the porous current collector, and a surface coating disposed on the side of the negative electrode active material layer away from the porous current collector, wherein the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes black phosphorus or a black phosphorus composite, and the surface coating includes a high temperature resistant material, and the high temperature resistant material includes a ceramic material and / or an organic polymer with a thermal decomposition temperature of ≥200°C. By disposing a negative electrode active material layer including black phosphorus or a black phosphorus composite on at least part of the surface of the porous current collector, lithium ions can be efficiently embedded and de-embedded, significantly improving the energy density. A surface coating including a ceramic material and / or an organic polymer with high thermal stability is coated on the surface of the negative electrode active material layer away from the porous current collector, which greatly improves the thermal stability of the negative electrode sheet, thereby solving the combustion safety problem caused by excessive temperature rise during battery charging and discharging. At the same time, ceramic materials and / or organic polymers with a thermal decomposition temperature of ≥200°C are distributed on the side of the negative electrode active material layer away from the porous current collector, which has a passivation effect on the surface of the negative electrode active material layer, enhances its electronic insulation performance, and can effectively inhibit the deterioration of the electrical performance of the battery under high-temperature storage conditions, and improve side reactions such as gas production. In addition, the setting of a surface coating containing ceramic materials and / or organic polymers with a thermal decomposition temperature of ≥200°C can not only promote better infiltration of the electrolyte on the negative electrode surface, but also enhance the ability of the negative electrode surface to absorb and retain the electrolyte, greatly improving the electrical performance and service life of the battery.
[0036] However, the setting of the surface coating will sacrifice the battery capacity and increase the internal resistance of the battery. The present application adopts a porous current collector to increase the roughness of the current collector surface, which can not only effectively increase the bonding force between the negative electrode active material layer and the current collector, reduce the shedding and pulverization of the negative electrode active material layer, but also significantly improve the energy density. The pore structure of the porous current collector can accommodate more negative electrode materials and provide additional lithium ion transmission channels, thereby increasing the capacity of the battery and improving the charge and discharge performance, thereby greatly avoiding the influence of the surface coating setting on the battery electrical performance, and can also improve the infiltration effect of the electrolyte, further improving the charge and discharge performance of the battery. The pore structure of the porous current collector can also improve safety, help improve the heat dissipation performance inside the battery, and reduce the temperature of the battery during the charge and discharge process. The combination of surface coating and porous current collector is expected to provide double protection for the safety performance of lithium-ion batteries.
[0037] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0039] Figure 1 is a schematic diagram of the structure of the negative electrode sheet in Example 1 of the present application;
[0040] Reference numerals: 10, current collector; 20, negative electrode active material layer; 30, surface coating. DETAILED DESCRIPTION
[0041] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0042] In the description of the present application, it should be noted that the terms "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present application. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0043] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0044] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0045] The present application provides a negative electrode sheet and a battery containing the same, which can improve the thermal stability of the negative electrode sheet, greatly improve the battery safety problem caused by spontaneous combustion, and also significantly improve the electrochemical performance and service life of the battery at high temperature, and improve the side reaction problems such as gas production. The technical solution adopted by the present application is as follows.
[0046] In a first aspect, the present application provides a negative electrode sheet, which includes a porous current collector, a negative electrode active material layer arranged on at least one surface of the porous current collector, and a surface coating arranged on the side of the negative electrode active material layer away from the porous current collector, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes black phosphorus or a black phosphorus composite, and the surface coating includes a high temperature resistant material, the high temperature resistant material includes a ceramic material and / or an organic polymer with a thermal decomposition temperature of ≥200°C.
[0047] It can be understood by those skilled in the art that by providing a negative electrode active material layer including black phosphorus or a black phosphorus composite on at least part of the surface of the porous current collector, lithium ions can be efficiently embedded and de-embedded, significantly improving the energy density. A surface coating including a ceramic material and / or an organic polymer with high thermal stability is coated on the surface of the negative electrode active material layer away from the porous current collector to greatly improve the thermal stability of the negative electrode sheet, thereby solving the combustion safety problem caused by excessive temperature rise of battery charging and discharging. At the same time, ceramic materials and / or organic polymers with a thermal decomposition temperature of ≥200°C are distributed on the side of the negative electrode active material layer away from the porous current collector, which has a passivation effect on the surface of the negative electrode active material layer, enhances its electronic insulation performance, and can effectively inhibit the deterioration of the electrical performance of the battery under high temperature storage conditions, and improve side reactions such as gas production. In addition, the setting of a surface coating comprising a ceramic material and / or an organic polymer with a thermal decomposition temperature of ≥200°C can not only promote the electrolyte to better infiltrate the negative electrode surface, but also enhance the ability of the negative electrode surface to absorb and retain the electrolyte, greatly improving the electrical performance and service life of the battery, which greatly improves the performance and service life of the battery. In addition, the negative electrode active material layer containing black phosphorus or a black phosphorus composite has a higher energy density than the negative electrode active material layer containing only graphite or other negative electrode active materials. However, the setting of the surface coating will sacrifice the battery capacity and increase the internal resistance of the battery. The present application adopts a porous current collector to increase the roughness of the current collector surface, which can not only effectively increase the bonding force between the negative electrode active material layer and the current collector, but also reduce the shedding and pulverization of the negative electrode material. The energy density can also be significantly improved. The structure of the porous current collector can accommodate more negative electrode materials and provide additional lithium ion transmission channels, thereby increasing the capacity of the battery and improving the charge and discharge performance, thereby greatly avoiding the influence of the surface coating setting on the battery electrical performance, and can also improve the infiltration effect of the electrolyte, further improving the charge and discharge performance of the battery. The porous current collector structure can also improve safety, help improve the heat dissipation performance inside the battery, and reduce the temperature of the battery during charging and discharging.
[0048] In an optional embodiment, the black phosphorus composite comprises one or more of a composite of black phosphorus and an organic material, and a composite of black phosphorus and an inorganic material. In an optional embodiment, the composite of black phosphorus and an inorganic material includes but is not limited to one or more of a black phosphorus-graphite composite and a black phosphorus-graphene composite. In an optional embodiment, the composite of black phosphorus and an organic material includes but is not limited to a black phosphorus-polyacrylonitrile composite, a black phosphorus-polyvinylidene fluoride composite, and a black phosphorus-polyimide composite. The present application prefers black phosphorus-graphite composite materials.
[0049] In an optional embodiment, the porous current collector has a thickness of 4-15 μm. For example, the thickness is 4 μm, 6 μm, 10 μm, 12 μm, 15 μm. The porous current collector can be copper foil or aluminum foil, preferably copper foil is suitable for lithium ion battery system, with a thickness of 6 μm, and preferably aluminum foil is used for sodium ion battery system, with a thickness of 12 μm.
[0050] In an optional embodiment, the pore size of the porous current collector is 50-100 μm, the pore spacing of the porous current collector is 100-200 μm, and the porosity of the porous current collector is 5-50%. For example, the pore size is 50 μm, 60 μm, 80 μm, 100 μm, the pore spacing is 100 μm, 130 μm, 200 μm, and the porosity is 5%, 10%, 20%, 30%, 40%, 50%. Preferably, the pore size of the porous current collector is 80-100 μm, the porosity is 20-30%, and the pore spacing is 130-200 μm.
[0051] In an optional embodiment, the particle size D90 of the negative electrode active material in the negative electrode active material layer is 20-800nm, and the particle size D50 is 300-600nm. For example, the particle size D50 is 300nm, 400nm, 500nm, 600nm. For example, the particle size D90 is 20nm, 400nm, 500nm, 600nm, 800nm. D50 is the particle size corresponding to the cumulative particle size distribution percentage of the negative electrode active material reaching 50%; D90 is the particle size corresponding to the cumulative particle size distribution percentage of the negative electrode active material reaching 90%. Both particle size D50 and particle size D90 are measured by a laser particle size analyzer.
[0052] This particle size distribution helps to increase the contact area between the negative electrode active material (such as black phosphorus or black phosphorus composite) and the electrolyte, and improves the diffusion rate of lithium ions. Among them, black phosphorus, as a two-dimensional material with a layered structure, has a more complex van der Waals force between layers. The phosphorus atoms in the black phosphorus layer are tightly bound by covalent bonds to form a stable pleated hexagonal honeycomb structure, which makes the layer have strong stability. However, the layers are bound to each other by weaker van der Waals forces. This weak interaction force allows black phosphorus to be easily peeled off into a single layer or multilayer structure under certain conditions.
[0053] In an optional embodiment, the ceramic material includes one or more of boehmite and alumina.
[0054] In an optional embodiment, the organic polymer having a thermal decomposition temperature of ≥200° C. comprises one or more of polyimide, polymethyl methacrylate, and polyvinylidene fluoride.
[0055] In an optional embodiment, the alumina has a particle size D50 of 0.2-6 μm and a specific surface area of 10-300 m 2 / g. The high temperature resistant material in the surface coating is preferably alumina, and the particle size D50 of alumina is controlled to be 0.2-6 μm, and the specific surface area is 10-300 m 2 / g, so that the coating thickness is uniform and the gaps between particles are uniform, which is conducive to smoother passage of lithium ions, thereby improving the charging and discharging efficiency of the battery while improving the thermal stability and safety of the battery. For example, the particle size D50 of aluminum oxide is 0.2, 2, 4, and 6 μm, and the specific surface area is 10, 15, 30, and 300 m 2 / g.
[0056] In an optional embodiment, the surface coating further includes one or more of a conductive agent and a binder.
[0057] In an optional embodiment, based on the total mass of the surface coating as 100%, the mass of the high temperature resistant material accounts for 70-96%, the mass of the conductive agent accounts for 1-15%, and the mass of the binder accounts for 3-15%. By controlling the mass proportions of the high temperature resistant material, the conductive agent and the binder within the above range, the internal resistance of the negative electrode sheet is significantly reduced, and the battery capacity is increased, so that the battery has low internal resistance and high battery capacity while improving thermal stability. For example, the mass proportions of the high temperature resistant material are 70%, 80%, 90%, and 96%, the mass proportions of the conductive agent are 1%, 5%, 10%, and 15%, and the mass proportions of the binder are 3%, 8%, 12%, and 15%.
[0058] In an optional embodiment, the negative electrode active material layer further includes one or more of a conductive agent and a binder.
[0059] In an optional embodiment, based on the total mass of the negative electrode active material layer being 100%, the mass of the negative electrode active material accounts for 90-99%, the mass of the conductive agent accounts for 0-2%, and the mass of the binder accounts for 1-8%. For example, the mass of the negative electrode active material accounts for 90%, 92%, 95%, and 99%, the mass of the conductive agent accounts for 0%, 1%, 1.5%, and 2%, and the mass of the binder accounts for 1%, 2%, 4%, 6%, and 8%.
[0060] In an optional embodiment, the binder in the negative electrode active material layer or the surface coating may be a conventional binder in the negative electrode. As an example, the binder may include at least one of polyvinylidene fluoride, polytetrafluoroethylene, and fluoroacrylate resin.
[0061] In an optional embodiment, the conductive agent in the negative electrode active material layer or the surface coating may be a conventional conductive agent in the negative electrode. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0062] In an optional embodiment, the permeability index R of the negative electrode sheet is 6.0 to 101, preferably 40 to 80; wherein the permeability index R is calculated by the following formula (I):
[0063]
[0064] in,
[0065] A is the pore size of the porous current collector, in μm;
[0066] B is the particle size D50 of the negative electrode active material, which is the particle size value corresponding to the cumulative distribution percentage from small to large reaching 50% in the particle size distribution, in nm;
[0067] W is the porosity of the porous current collector;
[0068] Among them, the porosity W has the following relationship per unit area through the pore size and pore spacing of the porous current collector:
[0069]
[0070] C is the pore spacing of the porous current collector, in μm.
[0071] The permeability index R can be used to measure the degree of matching between the structure of the negative electrode active material including black phosphorus or a black phosphorus composite and the porous current collector. Within the above range, the structure of the negative electrode active material and the porous current collector has good matching and stability, effectively increasing the bonding force between the negative electrode active material layer and the current collector, and reducing the shedding and pulverization of the negative electrode material. Especially within the preferred range, it means better matching and stability between the negative electrode active material including black phosphorus or a black phosphorus composite and the porous current collector, which means better cycle performance and higher energy density after the combination of the two. For example, the permeability index R can be 6, 10, 15, 20, 40, 50, 60, 80, 101.
[0072] In an optional embodiment, the single surface density of the negative electrode active material layer is 20 to 60 g / m 2 , the single-sided thickness is 10 to 30 μm. Different thicknesses and single-sided surface densities of negative electrode active material layers take into account different product applications. From thin to thick, both power and high energy density design can be taken into account, and the product application range is wide. For example, the single-sided surface density is 20g / m 2 , 30g / m 2 , 40g / m 2 , 50g / m 2 , 60g / m 2 The single-sided thickness is 10μm, 15μm, 20μm, 25μm, and 30μm.
[0073] In an optional embodiment, the surface coating has a single-sided surface density of 2 to 10 g / m 2 , the single-sided thickness is 1 to 7 μm. The single-sided surface density and thickness of the surface coating are set within the above range, which significantly reduces the influence of the surface coating setting on the internal resistance and battery capacity, so that the battery has low internal resistance and high battery capacity while improving thermal stability. The thicker the thickness, the better the safety of the negative electrode sheet, but the more capacity is sacrificed. For example, the single-sided surface density is 2g / m 2 , 4g / m 2 , 8g / m 2 , 10g / m 2 The single-side thickness is 1μm, 2.7μm, 5.3μm, and 7μm.
[0074] In a second aspect, the present application provides a battery, comprising the positive electrode sheet described in the first aspect of the present application, and further comprising a separator, a positive electrode sheet and an electrolyte.
[0075] In an alternative embodiment, the separator includes a base film and an adhesive layer provided on at least one surface of the base film; preferably, the adhesive layer contains one or both of polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA). In order to improve the bonding performance between the separator and the electrode sheet, and thus improve the safety performance of the negative electrode battery, adhesive layers are preferably provided on both sides of the base film.
[0076] In an alternative embodiment, the single-sided thickness of the adhesive layer is 1-3 μm. By way of example, the single-sided thickness of the adhesive layer is 1 μm, 2 μm, or 3 μm.
[0077] In an alternative embodiment, the relationship between the single-sided thickness y of the negative electrode active material layer and the single-sided thickness x of the adhesive layer is: y / x = 3.33-30. By controlling the single-sided thickness y of the negative electrode active material layer and the single-sided thickness x of the adhesive layer to satisfy the above relationship, the adhesion between the negative electrode sheet and the separator can be improved well, avoiding short circuit caused by contact between the positive and negative electrodes, and improving the battery safety. By way of example, y / x = 3.33, 5, 7.5, 15, 30.
[0078] In an alternative embodiment, a ceramic layer is further provided between the base film and the adhesive layer. The setting of the ceramic layer can further improve the thermal stability of the battery. The ceramic layer contains one or more of the ceramic materials including boehmite and alumina.
[0079] In an alternative embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer provided on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.
[0080] In some embodiments, the positive electrode active material is an oxide-based positive electrode material. By way of example, the oxide-based positive electrode material may be one or more of sodium nickel cobalt manganese oxide (Na(NiCoMn)O2, NCM), sodium lithium cobalt manganese oxide (NaCoO2), sodium nickel cobalt manganese oxide (Na2Ni2Co2O), lithium nickel cobalt manganese oxide (LiNi x Co y Mn z O2, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1).
[0081] In some embodiments, the positive electrode active material is a phosphate-based positive electrode material. By way of example, the phosphate-based positive electrode material may be one or more of sodium polyphosphate (P2Na2), LiFePO4, LiFe x Mn 1-x PO4 (where 0 < x < 1).
[0082] In some embodiments, the positive electrode active material is a Prussian blue compound. As an example, the Prussian blue compound may be a compound having sodium ions, transition metal ions, and cyanide ions (CN - ). The transition metal may be at least one of Mn, Fe, Cr, Ni, Co, and Cu. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0083] The electrolyte used in the battery of the present application may include any technology disclosed in the prior art.
[0084] The battery of the present application can be applied to a start-stop battery, a hybrid battery or a pure electric battery.
[0085] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit wt% represents the mass percentage. A soft-pack battery with a model of thickness*width*height=11mm*310mm*105mm is taken as an example.
[0086] Unless otherwise specified, the reagents, materials and instruments used in the following description are all conventional reagents, conventional materials and conventional instruments, which can be commercially obtained, and the reagents involved can also be synthesized by conventional synthesis methods. Among them, the black phosphorus-graphite composite can be commercially available, or it can be prepared by the following conventional method: black phosphorus and graphite are mixed (physical mixing) to obtain a black phosphorus-graphite composite. In the black phosphorus-graphite composite, the mass percentage of black phosphorus can be greater than 0wt% and less than 100wt%, such as 50wt%-99wt%, based on the mass of the black phosphorus-graphite composite; the mass percentage of graphite in the black phosphorus-graphite composite can be greater than 0wt% and less than 100wt%, such as 1wt%-50wt%, wherein, in the black phosphorus-graphite composite in the following embodiments and comparative examples, the mass percentages of black phosphorus and graphite are 95wt% and 5wt%, respectively, based on the mass of the black phosphorus-graphite composite.
[0087] Example A1
[0088] The negative electrode sheet provided in this embodiment includes a porous current collector, a negative electrode active material layer disposed on both sides of the porous current collector, and a surface coating disposed on the side of the negative electrode active material layer away from the porous current collector. Based on the total mass of the negative electrode active material layer being 100%, the negative electrode active material layer includes 95wt% of the negative electrode active material (black phosphorus-graphite composite), 1wt% of the conductive agent (conductive carbon black), and 4wt% of the binder (styrene-butadiene rubber). Based on the total mass of the surface coating being 100%, the surface coating includes 80wt% of the high temperature resistant material (aluminum oxide), 10wt% of the conductive agent (conductive carbon black), and 10wt% of the binder (styrene-butadiene rubber).
[0089] The type, thickness and pore parameters (pore size, pore spacing and porosity) of the porous current collector used to prepare the negative electrode sheet, the particle size D50 and D90 of the black phosphorus-graphite composite, and the particle size D50 and BET parameters of aluminum oxide are shown in Table 1. The preparation method is as follows:
[0090] The black phosphorus-graphite composite (D50 is 400nm, D90 is 700nm), conductive carbon black, and styrene-butadiene rubber were mixed and added into NMP to prepare the negative electrode active material layer slurry (solid content is 50%); aluminum oxide (particle size D50 is 4μm, BET is 15m 2 / g), conductive carbon black, and styrene-butadiene rubber are mixed and added into NMP to prepare a surface coating slurry (solid content is 51%);
[0091] The negative electrode active material layer slurry and the surface coating slurry were coated on one surface of a porous current collector (6um thick*650mm wide, pore size of 80μm, pore spacing of 130μm, and porosity of 30%) by double-layer coating technology and dried, and then coated on the other surface with the negative electrode active material layer slurry and the surface coating slurry and dried to obtain a negative electrode sheet. The single-sided surface density and single-sided thickness of the negative electrode active material layer, and the single-sided surface density and single-sided thickness of the surface coating are shown in Table 1.
[0092] The preparation method of the negative electrode sheet in Examples A2 to A4 is basically the same as that in Example A1, except that the pore size and pore spacing of the porous current collector are designed differently, resulting in different porosity and R of the porous current collector, as shown in Table 1 for details.
[0093] The preparation method of the negative electrode sheet in Examples A5 to A7 is basically the same as that in Example A1, the only difference is that the particle sizes D50 and D90 of the black phosphorus-graphite composite are different, resulting in different R, see Table 1 for details.
[0094] The preparation method of the negative electrode sheet in Examples A8 to A9 is basically the same as that in Example A1, the only difference being that the single-sided surface density and single-sided thickness of the surface coating are different, as shown in Table 1 for details.
[0095] The preparation method of the negative electrode sheet in Examples A10-A11 is basically the same as that in Example A1, except that the single-sided surface density and single-sided thickness of the negative electrode active material layer are different, resulting in different y / x, as shown in Table 1 for details.
[0096] The preparation method of the negative electrode sheet in Example A12 is basically the same as that in Example A1, except that black phosphorus (particle size D50 is 400 nm, D90 is 700 nm) is used instead of black phosphorus-graphite composite as the negative electrode active material, see Table 1 for details.
[0097] The preparation method of the negative electrode sheet in Example A13 is basically the same as that in Example A1, except that boehmite (particle size D50 is 4 μm, BET is 15 μm) is used. 2 / g) replaces alumina as high temperature resistant material, see Table 1 for details.
[0098] The preparation method of the negative electrode sheet in Example A14 is basically the same as that in Example A1, except that polyimide is used instead of alumina as the high temperature resistant material, as shown in Table 1 for details.
[0099] The preparation method of the negative electrode sheet in Examples A15-A16 is basically the same as that in Example A1, the only difference being that the thickness of the porous current collector is different, as shown in Table 1 for details.
[0100] The preparation method of the negative electrode sheet in Examples A17-A19 is basically the same as that in Example A1, except that the particle size D50 and BET of aluminum oxide are different, as shown in Table 1 for details.
[0101] Example A20
[0102] The negative electrode sheet provided in this embodiment is substantially the same as that in embodiment 1, except that the contents of the materials in the negative electrode active material layer and the surface coating are different. In this embodiment, based on the total mass of the negative electrode active material layer being 100%, the negative electrode active material layer comprises 99wt% of the negative electrode active material (black phosphorus-graphite composite), 0wt% of the conductive agent (conductive carbon black), and 1wt% of the binder (styrene-butadiene rubber). Based on the total mass of the surface coating being 100%, the surface coating comprises 70wt% of the high temperature resistant material (aluminum oxide), 15wt% of the conductive agent (conductive carbon black), and 15wt% of the binder (styrene-butadiene rubber).
[0103] Example A21
[0104] The negative electrode sheet provided in this embodiment is substantially the same as that in embodiment 1, except that the contents of the materials in the negative electrode active material layer and the surface coating are different. In this embodiment, based on the total mass of the negative electrode active material layer being 100%, the negative electrode active material layer comprises 90wt% of the negative electrode active material (black phosphorus-graphite composite), 2wt% of the conductive agent (conductive carbon black), and 8wt% of the binder (styrene-butadiene rubber). Based on the total mass of the surface coating being 100%, the surface coating comprises 96wt% of the high temperature resistant material (aluminum oxide), 1wt% of the conductive agent (conductive carbon black), and 3wt% of the binder (styrene-butadiene rubber).
[0105] Comparative Example A1
[0106] The negative electrode sheet provided in this comparative example includes a porous current collector, and negative electrode active material layers disposed on both sides of the porous current collector. The total mass of the negative electrode active material layer is 100%, and the negative electrode active material layer includes 95wt% of negative electrode active material (black phosphorus-graphite composite), 1.0wt% of conductive agent (conductive carbon black), and 4wt% of binder (styrene-butadiene rubber). The type, thickness and pore parameters (pore size, pore spacing and porosity) of the porous current collector used to prepare the negative electrode sheet, and the particle size D50 and D90 of the black phosphorus-graphite composite are shown in Table 1.
[0107] The preparation method is as follows:
[0108] The black phosphorus-graphite composite, conductive carbon black and styrene-butadiene rubber were mixed and added into NMP to prepare a negative electrode active material layer slurry (solid content of 50%);
[0109] The negative electrode active material layer slurry is coated on the two surfaces of the porous current collector in turn by using a single-layer coating technique and then dried in an oven to obtain a negative electrode sheet. The single-sided surface density and single-sided thickness of the negative electrode active material layer are shown in Table 1.
[0110] The preparation method of the negative electrode sheet in Comparative Example A2 is basically the same as that in Example A1, except that the current collector is not perforated and copper foil is directly used.
[0111] The preparation method of the negative electrode sheet in Comparative Example A3 is basically the same as that in Comparative Example A1, except that the current collector is not perforated and copper foil is directly used.
[0112] Example B1
[0113] The battery provided in this embodiment is prepared by the following method:
[0114] Step 1: Prepare the positive electrode
[0115] The lithium iron phosphate positive electrode material, the conductive agent (conductive carbon black: SP), and the adhesive (polyvinylidene fluoride: PVDF) were dispersed in N-methylpyrrolidone at a mass ratio of 97%:1%:2% to obtain a uniform positive electrode slurry. The solid content of the positive electrode slurry was 60%. The positive electrode slurry was evenly coated on the surface of the aluminum foil. The single-sided surface density was 280g / m 2 , after drying and rolling, the positive electrode sheet is obtained.
[0116] Step 2: Battery Preparation
[0117] The negative electrode sheet prepared in Example A1, the positive electrode sheet prepared in the first step and a PVDF coated separator (purchased from Xingyuan Material Company, double-layer coated, the thickness of the coated layer on one side is x=2 μm) were placed on the surface of the negative electrode sheet prepared in Example A1. , The relationship between the single-sided thickness y of the negative electrode active material layer and the single-sided thickness x of the coating layer is: y / x=7.5) is assembled into a roll core, placed in a shell, baked, injected with liquid (the electrolyte was purchased from Tianci, brand HAT11), and hot-pressed at 45 degrees. The formation pressure is 2000kgf, and the formation steps are as follows: preheat for 30 minutes, charge at 0.2C for 5% SOC in the first step, charge at 0.5C for 20% SOC in the second step, charge at 1C for 60% SOC in the third step, and stand for 5 minutes to end the formation. Use two seals to remove the battery airbag belt and then sort it; the sorting steps are as follows: 300kgf pressure at room temperature, the first step is to leave it for 5 minutes, the second step is 1C constant current and constant voltage charging to 3.65V, 0.05C cut-off, the third step is to leave it for 10 minutes, the fourth step is 1C constant current discharge to 2.5V, record the capacity, the fifth step, 0.5C constant current and constant voltage charging to 30% SOC, the sixth step, leave it for 10 minutes to get the required battery.
[0118] The preparation methods of the batteries in Examples B2 to B21 are similar to those in Example B1, except that the negative electrode sheets are prepared using the negative electrode sheets prepared in Examples A2 to A21 of the present application instead of the negative electrode sheets in Example A1.
[0119] The preparation method of the battery in Example B22 is basically the same as that in Example B1, the only difference being that the battery is prepared using a separator with a single-side coating layer thickness of x=1 μm, resulting in a different y / x.
[0120] The preparation method of the battery in Example B23 is basically the same as that in Example B1, the only difference being that the battery is prepared using a separator with a single-side coating layer thickness of x=3 μm, resulting in a different y / x.
[0121] The preparation method of the battery in Example B24 is basically the same as that in Example B1, the only difference is that a PMMA coated diaphragm (purchased from Xingyuan Materials Company, double-layer coated, single-side thickness of the coated layer x=2 μm) is used instead of a PVDF coated diaphragm.
[0122] The preparation methods of the batteries in Comparative Examples B1 to B3 are similar to those in Example B1, except that the batteries are prepared using the negative electrode sheets prepared in Comparative Examples A1 to A3 of the present application instead of the negative electrode sheet in Example A1.
[0123] Table 1 Performance parameters of negative electrode
[0124]
[0125]
[0126]
[0127] Test Case
[0128] 1. Battery capacity, battery internal resistance, mass energy density
[0129] ① Charge the lithium-ion battery at 1C constant current and constant voltage at 25℃ to 3.65V, cut off at 0.05C, and then discharge at 1C to 2.5V. The discharged capacity is recorded as the battery capacity;
[0130] ② Charge the lithium-ion battery to 30% SOC at 0.5C at 25℃, and use a lithium battery AC internal resistance tester to test the internal resistance of the battery.
[0131] ③Calculate mass energy density based on capacity and battery weight.
[0132] 2. Cycle test
[0133] The battery was charged at 1C constant current to an upper voltage limit of 3.65V at room temperature, cut off at a constant voltage of 0.05C, left for 10 min, discharged at 1C constant current to a lower voltage limit of 2.5V, left for 10 min, and the charge-rest-discharge-rest steps were repeated. The capacity retention rate comparison results for 500 cycles were recorded.
[0134] 3. 3C fast charge constant current ratio
[0135] The battery is charged at room temperature using a 3C constant current to an upper limit voltage of 3.65V, and then charged at a constant voltage to a cutoff of 0.05C, and the constant current ratio is calculated; constant current ratio = constant current charging capacity / (constant current charging capacity+constant voltage charging capacity)*100%.
[0136] 4. High temperature storage
[0137] The battery was charged at 1C constant current to an upper limit voltage of 3.65V at room temperature, then switched to 0.05C constant voltage cutoff, stored in an 85-degree constant temperature box for 96 hours, taken out and cooled at room temperature for 24 hours, and discharged at 1C to 2.5V to record the residual capacity retention rate and test thickness expansion rate.
[0138] 5. Heating test
[0139] After the battery cell is fully charged (0.33C charging 3.65V cut-off 0.05C), the battery is placed in a blast oven, and the temperature is raised from room temperature to (130±2)℃ at a rate of (5±2)℃ / min, and kept at this temperature for 30min. If the battery does not explode or catch fire, it passes, otherwise it fails. Five batteries of each embodiment and comparative example are tested in parallel, and the pass rate is calculated.
[0140] 6. Short circuit test
[0141] After the battery cell is fully charged (0.33C charging 3.65V cut-off 0.05C), under the condition of ambient temperature (25±5)℃, the fully charged battery is connected to the positive and negative terminals of the battery with a resistance <5mΩ wire for 10 minutes, and then the short-circuit device is removed and the battery is observed for another 1 hour. If the battery does not explode or catch fire during the period, it passes, otherwise it fails. Five batteries of each embodiment and comparative example are tested in parallel, and the pass rate is calculated.
[0142] 7. Overcharge test
[0143] After the cell is fully charged (0.33C charging to the upper voltage limit and 0.05C cut-off), the fully charged battery is charged at 1C constant current until the voltage reaches 1.3 times the charging termination voltage specified in the enterprise technical conditions (specifically 3.65V) and the test is stopped; the battery is required to pass if it does not explode or catch fire, otherwise it fails. Five batteries of each embodiment and comparative example are tested in parallel, and the pass rate is calculated.
[0144] The test results are shown in Table 2.
[0145] It can be seen from Table 2 that the combination of a surface coating comprising a high temperature resistant material and a porous current collector coated on the surface of the negative electrode active material layer including black phosphorus or a black phosphorus composite can significantly improve the safety performance, storage performance, and cycle and charging performance of the battery. In particular, the introduction of the porous current collector solves the problems of capacity sacrifice and increased internal resistance caused by the surface coating.
[0146] Table 2 Battery test results
[0147]
[0148]
[0149] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet includes a porous current collector, a negative electrode active material layer arranged on at least one surface of the porous current collector, and a surface coating arranged on the side of the negative electrode active material layer away from the porous current collector, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes black phosphorus or a black phosphorus composite, and the surface coating includes a high temperature resistant material, the high temperature resistant material includes a ceramic material and / or an organic polymer with a thermal decomposition temperature of ≥200°C.
2. The negative electrode sheet according to claim 1, characterized in that: The black phosphorus composite comprises one or more of a composite of black phosphorus and an organic material and a composite of black phosphorus and an inorganic material; Preferably, the composite of black phosphorus and inorganic material comprises one or more of a black phosphorus-graphite composite and a black phosphorus-graphene composite; Preferably, the composite of black phosphorus and organic material comprises a black phosphorus-polyacrylonitrile composite, a black phosphorus-polyvinylidene fluoride composite, and a black phosphorus-polyimide composite.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: The thickness of the porous current collector is 4-15 μm; and / or the pore size of the porous current collector is 50-100 μm, and the pore spacing of the porous current collector is 100-200 μm; the porosity of the porous current collector is 5-50%; and / or the particle size D90 of the negative electrode active material in the negative electrode active material layer is 20-800 nm, and the particle size D50 is 300-600 nm.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The ceramic material includes one or more of boehmite and alumina; the organic polymer with a thermal decomposition temperature of ≥200° C. includes one or more of polyimide, polymethyl methacrylate, and polyvinylidene fluoride; Preferably, the alumina has a particle size D50 of 0.2-6 μm and a specific surface area of 10-300 m 2 / g.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The surface coating also includes one or more of a conductive agent and a binder; preferably, based on the total mass of the surface coating as 100%, the mass of the high temperature resistant material accounts for 70-96%, the mass of the conductive agent accounts for 1-15%, and the mass of the binder accounts for 3-15%.
6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The negative electrode active material layer also includes one or more of a conductive agent and a binder; preferably, based on the total mass of the negative electrode active material layer being 100%, the mass of the negative electrode active material accounts for 90-99%, the mass of the conductive agent accounts for 0-2%, and the mass of the binder accounts for 1-8%.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The permeability index R of the negative electrode sheet is 6.0 to 101, preferably 40 to 80; Wherein, the permeability index R is calculated by the following formula (I): in, A is the pore size of the porous current collector, in μm; B is the particle size D50 of the negative electrode active material, which is the particle size value corresponding to the cumulative distribution percentage from small to large reaching 50% in the particle size distribution, in nm; W is the porosity of the porous current collector; Among them, the porosity W has the following relationship per unit area through the pore size and pore spacing of the porous current collector: C is the pore spacing of the porous current collector, in μm.
8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The single surface density of the negative electrode active material layer is 20 to 60 g / m 2 , the single-sided thickness is 10 to 30 μm; and / or the single-sided surface density of the surface coating is 2 to 10 g / m 2 , the single-side thickness is 1 to 7 μm.
9. A battery, characterized in that: The invention comprises the negative electrode sheet as described in any one of claims 1 to 7, and also comprises a separator, a positive electrode sheet and an electrolyte.
10. The battery according to claim 9, characterized in that The diaphragm includes a base film, and a rubber coating layer disposed on at least one surface of the base film; Preferably, the coating layer contains one or two of polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA); preferably, the thickness of the coating layer on one side is 1 to 3 μm; more preferably, the relationship between the thickness y of the negative electrode active material layer on one side and the thickness x of the coating layer on one side is: y / x=3.33 to 30.